1963
DOI: 10.1080/00049536308255469
|View full text |Cite
|
Sign up to set email alerts
|

Binocular interaction and serial addition

Abstract: Sampson has demonstrated that, for very brief exposure times only, the use of the non-dominant eye, determined by an aiming test, results in poorer performance in a serial addition task. The present study reports that when fixation points are supplied, the differences between the dominant and non-dominant eye, at these very brief exposure times, disappear. Sampson concluded that information from the non-dominant eye is integrated more slo,wly than that from the dominant eye. The present study questions the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1963
1963
1980
1980

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…On the other hand, if more weight were given to impulses from the left eye, the opposite would hold. Since all subjects were right eye dominant, as determined by the aiming test and the Foley and Ross (1963) adaptation of the serial addition test, the former would appear to be the case. Sherrington (1904) had concluded that "each uniocular mechanism develops independently ... a sensual image of considerable completeness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, if more weight were given to impulses from the left eye, the opposite would hold. Since all subjects were right eye dominant, as determined by the aiming test and the Foley and Ross (1963) adaptation of the serial addition test, the former would appear to be the case. Sherrington (1904) had concluded that "each uniocular mechanism develops independently ... a sensual image of considerable completeness.…”
Section: Discussionmentioning
confidence: 98%
“…A recent attempt by Sampson (1962) [but see also Foley and Ross (1963)] to account for the Sherrington effect on the assumption that information from the non-dominant eye is integrated centrally more slowly than information from the dominant eye makes a precise definition of the function necessary. Further, it is important to define not only the function for phase differences between 0° and 180°, but also the function for phase differences between 180° and 360°.…”
mentioning
confidence: 99%
“…Dominance relations as determined on a sighting test may have limited predictive value for performance on other visual tasks (cf. Foley & Ross, 1963).…”
mentioning
confidence: 99%